ANALYSIS OF STUDENT DIFFICULTIES IN WRITING THESIS IN ENGLISH EDUCATION PROGRAM AT IAIN PAREPARE - Muh Riswan; Tulus Hermawan; Aswar Aswar (Journal of English Education, 2026)
Thesis writing is a central academic requirement for English education students, yet many students experience difficulties in converting ideas, research procedures, and academic language into a coherent thesis manuscript. This study aimed to describe the types of difficulties experienced by English Education Program students at IAIN Parepare in writing a thesis and to identify the factors that caused these difficulties. The study applied a descriptive quantitative design. Data were collected through a questionnaire administered to 25 seventh-semester students and analyzed using descriptive statistics, mean scores, and percentages. The findings show that academic difficulties were slightly more dominant than non-academic difficulties. Academic difficulties accounted for 51.68% of the total difficulty score and included academic writing style, grammatical rules, paraphrasing, and limited vocabulary. Non-academic difficulties accounted for 48.32% and included low motivation and limited feedback. The causal factors were also relatively balanced, with internal factors reaching 51.23% and external factors reaching 48.77%. The study concludes that thesis-writing support should integrate academic writing training, systematic feedback, vocabulary development, and stronger supervisory and institutional support.